2012
DOI: 10.3892/ol.2012.658
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of anoikis resistance through CD147 upregulation: A new mechanism underlying metastasis of hepatocellular carcinoma cells

Abstract: Abstract. Acquisition of anoikis resistance is a prerequisite for the metastasis of hepatocellular carcinoma (HCC) cells. Activation of growth factor signaling pathways and rearrangement of the cytoskeleton have been reported as vital steps in this process. However, key molecules involved in anoikis resistance remain to be determined. The aim of this study was to investigate the effect of CD147 on HCC cells resistant to anoikis. The human SMMC-7221 human HCC cell line was used. Immunofluorescence was used to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 33 publications
0
25
0
Order By: Relevance
“…Previous findings have indicated that CD147 expression protects breast cancer cells from anoikis, at least in part, by a mitogen-activated protein kinase-dependent reduction of Bim, which is a proapoptotic BH3-only protein, and that knockdown of CD147 expression by RNA interference sensitized cancer cells to anoikis through the activation of caspase-3 [ 52 ]. Ke et al found that CD147 expression was significantly higher in hepatocellular carcinoma cells (SMMC-7721) resistant to anoikis compared with the parental cells, and that CD147 knockdown by siRNA also remarkably induced cell anoikis, partially via inactivation of the PI3K/Akt signaling pathway [ 53 ]. In summary, the acquisition of anoikis resistance through upregulation of CD147 may represent a newly recognized mechanism underlying the metastasis of malignant tumor cells.…”
Section: Cd147 In Tumorsmentioning
confidence: 99%
“…Previous findings have indicated that CD147 expression protects breast cancer cells from anoikis, at least in part, by a mitogen-activated protein kinase-dependent reduction of Bim, which is a proapoptotic BH3-only protein, and that knockdown of CD147 expression by RNA interference sensitized cancer cells to anoikis through the activation of caspase-3 [ 52 ]. Ke et al found that CD147 expression was significantly higher in hepatocellular carcinoma cells (SMMC-7721) resistant to anoikis compared with the parental cells, and that CD147 knockdown by siRNA also remarkably induced cell anoikis, partially via inactivation of the PI3K/Akt signaling pathway [ 53 ]. In summary, the acquisition of anoikis resistance through upregulation of CD147 may represent a newly recognized mechanism underlying the metastasis of malignant tumor cells.…”
Section: Cd147 In Tumorsmentioning
confidence: 99%
“…Increased expression of CD147 was shown to correlate with enhanced tumor progression and poor prognosis in different cancers [ 6 8 ]. Thus, an attractive way to curb tumor progression is through suppression of the CD147-dependent cell proliferation, invasion and metastasis by RNAi-mediated silencing [ 5 , 9 ] and eventually induce cell apoptosis due to detachment of anchorage-dependent cell from the surrounding extracellular matrix [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that HAb18G/CD147 pay an important role in cancer metastasis and progression. Recently, we showed that HAb18G/CD147 promote epithelial-mesenchymal transition (21), anoikis resistance and anchorage-independent growth in vitro (22, 23) and tumorigenic potential of liver cancer in vivo (21), indicating a possible role of HAb18G/CD147 in tumor initiation.…”
Section: Introductionmentioning
confidence: 99%